720 Actigraphy to Evaluate Sleep in the Inpatient Setting: A Systematic Review. (3rd May 2021) - Sussman, Sarah; Fares, Elie; Ananth, Ashwin; Boon, Maurits; Fast, Zhanna; Huntley, Colin
Abstract: Introduction: Sleep disruption is common among hospitalized patients due to psychological, physiological, and environmental reasons including illness, pain, anxiety, invasive interventions, frequent monitoring, and stimuli, especially noise and light. The AASM has published guidelines for the use of actigraphy in the outpatient setting, but there is a paucity of literature evaluating the validity of actigraphy in inpatients. We sought to summarize the evidence surrounding the use of actigraphy for inpatient sleep evaluation. Methods: Systematic review was conducted according to the Preferred Reporting of Systematic Reviews and Meta-Analysis (PRISMA) guidelines. Databases were queried by two independent reviewers for English-language studies published between 1990 and 2020. The initial search screened for all occurrences of "actigraphy AND sleep AND hospital" then was further refined to include studies of actigraphy used for monitoring in the inpatient hospital setting and exclude studies evaluating actigraphy in outpatient, rehabilitation, immediate postoperative, or intensive care unit settings. Results: 1221 were screened from initial search results. 48 articles were identified through screening of abstracts. Full-text review of the articles was then completed. Of the 48 articles, a total of 12 studies examined general medical inpatients, 12 studies examined inpatients with neurologic disorders, 5 studies examined inpatients with cancer, 6 studies examined patients with mental illness, 9 studies examined elderly patients, and 4 studies examined other defined populations (pregnancy, trauma, liver transplantation, and hip arthroplasty). We summarize the qualitative findings of inpatient actigraphy as it relates to each of these populations. Commonly reported outcome measures were total sleep time (TST), number of nighttime awakenings, and concordance with polysomnography (PSG). Conclusion: We summarize the existing evidence for the use of actigraphy in the inpatient setting. Actigraphy may provide a simple and effective method for screening of sleep disorders in the inpatient setting. With regard to the published literature, there is support for the use of actigraphy in the inpatient setting in certain patient populations, especially traumatic brain injury. Variation in data output of actigraphy devices and outcome measures presents a barrier to meta-anaylsis of pooled data. Standardization of outcome measures will allow for effective synthesis of future studies. Support (if any):